STUDI TINGKAT KINERJA PEGAWAI DINAS PERPUSTAKAAN DAN ARSIP PROVINSI KALIMANTAN TENGAH - Devi Avita Sari; Slamet Winaryo; Piter Joko Nugroho (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2023)
This study aims to determine the level of performance of employees of the Central Kalimantan Province Library and Archives Service, seen from the dimensions: (1) Service Orientation, (2) Integrity, (3) Commitment, (4) Discipline, and (5) Cooperation. The type of research used is descriptive quantitative. The population in this study were employees at the Central Kalimantan Province Library and Archives Service, totaling 18 people with Echelon III and IV status, where all populations were samples (total sample). The data collection technique is a questionnaire / questionnaire. The results showed that in general the performance level of employees at the Central Kalimantan Province Library and Archives Service was in the